1996
DOI: 10.1002/j.1460-2075.1996.tb00658.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional analyses of active site residues of human lysosomal aspartylglucosaminidase: implications for catalytic mechanism and autocatalytic activation.

Abstract: Aspartylglucosaminidase (AGA) is a lysosomal asparaginase that participates in the breakdown of glycoproteins by cleaving the amide bond between the asparagine and the oligosaccharide chain. Active AGA is an (alphabeta)2 heterotetramer of two non‐identical subunits that are cleaved proteolytically from an enzymatically inactive precursor polypeptide. On the basis of the three‐dimensional structure recently determined by us, we have here mutagenized the putative active site amino acids of AGA and studied by tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 15 publications
(25 reference statements)
5
85
0
Order By: Relevance
“…The crystal structures of human and bacterial GA show a similar structural frame of an ␣␤␤␣-sandwich, common to all the Ntn hydrolases (7)(8)(9)(10). One intriguing aspect of GA is that a single chain precursor is processed by intramolecular autoproteolysis that generates the 17-kDa ␣-and 15-kDa ␤-subunits and exposes the active site threonine at the newly generated N-terminal end of the ␤-subunit (11,12). A similar mechanism is utilized in protein splicing that involves two concerted autocleavages and one ligation of the polypeptide chain (13,14).…”
Section: Glycosylasparaginase (Ga)mentioning
confidence: 99%
“…The crystal structures of human and bacterial GA show a similar structural frame of an ␣␤␤␣-sandwich, common to all the Ntn hydrolases (7)(8)(9)(10). One intriguing aspect of GA is that a single chain precursor is processed by intramolecular autoproteolysis that generates the 17-kDa ␣-and 15-kDa ␤-subunits and exposes the active site threonine at the newly generated N-terminal end of the ␤-subunit (11,12). A similar mechanism is utilized in protein splicing that involves two concerted autocleavages and one ligation of the polypeptide chain (13,14).…”
Section: Glycosylasparaginase (Ga)mentioning
confidence: 99%
“…On the other hand, mutagenesis studies of aspartylglucosaminidases have established that substitution of the equivalent of Thr 230 by Ala does not abolish autoproteolysis, although it makes it less efficient (19,47). Moreover, it was reported that although this mutation completely inhibits the catalytic activity of the human enzyme (47), the bacterial homolog retains 30% of its original activity (19).…”
Section: Conformation Of Thr 179 -A Theoretically Modeled Thrmentioning
confidence: 99%
“…As a conclusion, it has been postulated that in aspartylglucosaminidases, the Thr residue is required for proper positioning of Asp 151 (20). With regard to Thr 197 , an alanine substitution of its equivalent in aspartylglucosaminidase resulted in a processing-defective human enzyme (47), whereas for the bacterial protein, only the processing rate was affected, whereas the reaction product was unchanged (19). Those observations suggest that none of these Thr residues is a universal and absolute prerequisite for the autoproteolytic process.…”
Section: Conformation Of Thr 179 -A Theoretically Modeled Thrmentioning
confidence: 99%
“…Bound water enhances the nucleophilicity of the Thr O␥ at the ϩ1 position in the PS precursor (4), whereas the Asp-151 carboxylate at the Ϫ1 position promotes the nucleophilicity of the Thr-152 at the ϩ1 position in the GA precursor (7). Consequently, the hydroxyl of the catalytic Thr attacks the adjacent scissile peptide bond to carry out intramolecular cleavage (4,(7)(8)(9)(10).…”
Section: Conformation Of the F177␤p Precursor Cad Forces The Eliminatmentioning
confidence: 99%